Flexible supercapacitor electrodes based on MoS2-intercalated rGO membranes on Ti mesh. (January 2018) - Lamberti, Andrea
Abstract: The fabrication of innovative 2D materials-based composite electrodes is here presented. Graphene oxide (GO) and molybdenum disulfide (MoS2 ) were dispersed in water-based solution and after drop casting onto a titanium (Ti) mesh and fast GO reduction a flexible rGO/MoS2 electrode was obtained and exploited for supercapacitor application. The structural, physical and chemical properties of the samples were analyzed by electron microscopy, energy dispersive X-ray spectroscopy, contact angle measurements and infrared spectroscopy while electrochemical characterizations were conducted on the assembled device in two electrodes configuration. The promising electrochemical performance observed pave the way to the exploitation of the proposed approach for flexible and wearable supercapacitors fabrication.